PENGARUH EARNING PER SHARE, RETURN ON ASSETS DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2024 - Kornelia, Mieke; Kasir, Kasir (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the effect of Earnings Per Share (EPS), Return on Assets (ROA), and Current Ratio (CR) on the stock prices of companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2024. The research method used is a quantitative approach with an associative method, using secondary data in the form of published annual financial reports. The analysis was carried out using multiple linear regression tests to determine the partial and simultaneous effects of these variables on stock prices. The results of the study indicate that EPS has a positive and significant effect on stock prices, while ROA has a negative and significant effect. Meanwhile, CR does not have a significant effect on stock prices. However, simultaneously, the three variables have a significant effect on stock prices. This study provides implications that earnings per share performance and asset utilization efficiency are important to consider in assessing stock prices, while company liquidity has less direct influence. Keywords: Earning Per Share (EPS), Return On Assets (ROA), Current Ratio (CR), Stock Prices